Pengaruh Media Edmodo Dalam Pembelajaran PPKN Terhadap Karakter Mandiri Siswa Pada SMA N 1 Mutiara - Cut Anisaturrahmi; Ruslan Ruslan; Hasbi Ali (Journal on Education, 2023)
The reality that occurs at this time, there are still many students who are not independent in learning. The low level of student activeness is caused by students' use of discussion-informative learning methods applied to activities. The study aims to see the difference between Civics learning using conventional media and Civics learning using edmodo media in improving students' independent character. This research is a quantitative experimental research with a quasi-experimental design with a nonequivalent control group design. The experimental population is the entire X MIPA class of SMA N 1 Mutiara by taking a sample of 2 classes (control class and experimental class) on condition that the class is held by the same subject teacher. Tests include pre tests and post tests, as well as making observations and distributing questionnaires. To see a significant difference between the control class and the experimental class, the Wilcoxon Match Pair test was conducted at a significance level of 0.005, after the research prerequisites were met. Based on the research, it is known that there is a significant difference between Civics learning using conventional media and Civics learning using edmodo media in increasing student independence at SMA N 1 Mutiara, where the class learning using edmodo media is higher than the class learning using conventional media.